An Exercise in Questioning one’s own Action Following Smith’s Framework of Critical Reflection - Biazi, Terezinha M. D. (The ESPecialist, 2012)
This article presents an exercise of critical reflection the researcher carried out with a public school teacher, engaged in a programme of continuing education. The study focuses fundamentally on how the researcher, through questionings guided by the four forms of actions of critical reflection developed by Smith (1992), could contribute to the teacher’s reflection on her own practice. The results show that the quality of the questioning and the way of conducting such questioning had a crucial role in the implementation of Smith’s framework of critical reflection.